Investigation of Geological Diversity Based on the Degree of Sensitivity and the Amount of Equilibrium and Resilience of the Geosystem (Case study: The Eastern Kopet-Dagh Zone) - Sima Tavsoli; Adel Sepehr; Abbas Ghaderi (Geoconservation Research)
Geomorphological principles show that the earth's surface is not fixed and changes over time. The physical elements of the earth's surface, from microscopic components such as minerals to macroscopic phenomena such as landforms, are all part of geodiversity. Landform equilibrium and resilience are related to the resistance to the erosion pattern. In other words, morphogenic processes in low resilience geosystems cause landform changes. Resilience is usually considered as increasing stability and reducing sensitivity; measuring the amount and quality of that issue is essential in protecting perspectives. Here, we evaluate the geo-diversity of the Eastern Kopet-Dagh Mountains in northeastern Iran based on the geosystem's degree of sensitivity, equilibrium, and resilience. In this study, using overlapping information layers, we classified each indicator into three degrees of sensitivity after selecting suitable indicators. Then, a geological diversity map was prepared by combining the data into two sub-sets of geosystem sensitivity and protection. We find that about 41% of the Eastern Kopet-Dagh Mountains, equivalent to 7800 km2, have a high degree of sensitivity, more in the southern half of the study area than in the northern half. In these sensitive areas the slightest change by disturbance can overwhelm the recovery potential and change the state of the geosystem. Consistency of research findings with field visits shows the necessity of proper management and exploitation of the mentioned areas to prevent critical conditions and further expansion of vulnerable regions.